Photoimmunosuppression of contact hypersensitivity. (April 2006) - Norval, Mary
Contact hypersensitivity is characterized by an antigen-specific T cell-mediated skin inflammation that occurs at the site of challenge with a hapten in individuals who have already generated an immune response to that hapten. A complex cascade follows ultraviolet irradiation of the skin and topical application of a hapten, ending in suppression of the contact hypersensitivity response. A variety of photoreceptors at the body surface initiate the process: these have been identified as DNA, trans -urocanic acid and membrane components. Secondary steps follow, such as the production of a range of soluble immune mediators and changes in the number, phenotype and function of Langerhans cells, dendritic cells and macrophages. The final effector mechanisms include the expression of immunosuppressive cytokines, a change from a type 1 cytokine profile to type 2, the induction of hapten-specific T-regulatory cells and defective antigen presentation. The consequences of immunomodulation for skin cancer are considered. Finally, knowledge regarding ultraviolet-induced immunomodulation is applied to phototherapy for psoriasis and several questions requiring further investigation are identified.